КОНЦЕПЦІЯ ПРИРОДООРІЄНТОВАНИХ РІШЕНЬ В ІННОВАЦІЙНІЙ ДІЯЛЬНОСТІ ЛІСОГОСПОДАРСЬКИХ ПІДПРИЄМСТВ (Економічний часопис Волинського національного університету імені Лесі Українки, 2025)
Introduction. It is important to systematically introduce the concept of nature-based solutions into the activities of forestry enterprises in Ukraine to achieve the principles of sustainable development, preservation of biodiversity and ecological sustainability of natural ecosystems, as well as to ensure the economic and social well-being. Innovative solutions increase labor productivity, optimize production processes, reduce resource consumption, contribute to the development of effective and efficient approaches to the management system, increase the competitiveness of forestry enterprises and reduce the negative impact on the environment.The purpose of the article is the theoretical and methodological principles and practical aspects of the implementation of nature-based solutions in the activities of forestry enterprises as a response to modern challenges and threats in the field of forestry.Methods. The research used such methods as description, explanation, comparison, system approach, financial analysis.Results. Nature-based solutions (NBS) are actions that protect, conserve, restore and sustainably use natural ecosystems, contributing to solving social, economic and environmental challenges. A financial analysis of three NBSs was performed: street green furniture, green pergolas, forbs, which are aimed at creating environmentally friendly facilities. It is argued that the proposed solutions correspond to the sustainable use of forest resources and the preservation of the natural environment. It was determined that nature-based approaches to management include biodiversity conservation, creation of ecological corridors, development of sustainable forestry, environmentally friendly production, monitoring and control, and innovative management.Conclusions. Today, the forestry of Ukraine operates in a VUCA-World, which requires to be flexible, innovative and able to respond quickly to changes. Innovation is an important step to ensure the sustainable development of the forest industry and the preservation of natural ecosystems for future generations.
Keywords: інновації, природоорієнтовані рішення, стратегія, бізнес планування, управління проєктами, фінансовий аналіз, менеджмент.